Evidence of phytoplankton blooms under Antarctic sea ice - Horvat, Christopher; Bisson, Kelsey; Seabrook, Sarah; Cristi, Antonia; Matthes, Lisa C. (Frontiers in Marine Science, 2022)
Areas covered in compact sea ice have often been assumed to prohibit upper ocean photosynthesis. Yet under-ice phytoplankton blooms (UIBs) have increasingly been observed in the Arctic, driven by anthropogenic changes to the optical properties of Arctic sea ice. Here we show the Southern Ocean may also support widespread UIBs. Using under ice-enabled BGC-Argo float data, we detail numerous high phytoplankton growth events below compact sea ice preceding seasonal ice retreat and categorize 12 multi-week events with levels comparable to previously-observed Arctic UIBs. Using joint light, sea ice, and ocean conditions obtained from ICESat-2 laser altimetry and 11 climate model contributions to CMIP6, we find that more than 4 million square kilometers of the compact-ice-covered Southern Ocean could support these events in late spring and early summer.